Post-intensive care syndrome (PICS) – prevention and treatment - Jędrocha, Karolina; Wojnar-Gruszka, Katarzyna; Wojtas, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Interventions are made in the intensive care unit (ICU) to stabilise the patient’s condition in a life-threatening situation. Unfortunately, hospitalisation in this unit – often prolonged – can lead to sequelae that limit and hinder the patient’s ability to temporarily or permanently function in a number of activities, referred to as post-intensive care syndrome (PICS). Medical developments point to the possibility and necessity of interventions aimed at prevention, early recognition, and treatment of this syndrome. The presented paper is aimed at introducing the essence of PICS prevention, treatment, and intervention. The available literature presents possible and necessary interventions to prevent and treat this syndrome based on the use of standardised tools to assess the patient’s condition, implement procedures, standards of management, and evaluation of individual therapeutic plans.